x+(26+x)=64

Simple and best practice solution for x+(26+x)=64 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+(26+x)=64 equation:


Simplifying
x + (26 + x) = 64

Remove parenthesis around (26 + x)
x + 26 + x = 64

Reorder the terms:
26 + x + x = 64

Combine like terms: x + x = 2x
26 + 2x = 64

Solving
26 + 2x = 64

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-26' to each side of the equation.
26 + -26 + 2x = 64 + -26

Combine like terms: 26 + -26 = 0
0 + 2x = 64 + -26
2x = 64 + -26

Combine like terms: 64 + -26 = 38
2x = 38

Divide each side by '2'.
x = 19

Simplifying
x = 19

See similar equations:

| 5w^2+12w^2= | | 8(y-1)=3y+17 | | -5k-2k=14 | | -4-9/3=-7 | | -7(n+3)=-34+6n | | 64x^2-192x=0 | | 4.7=30 | | .4*-.03= | | 7x+22=11x+68 | | V-39=-17 | | 3=k+4+5 | | 21x+3=12x+6 | | -(1-7x)=4x-13 | | 2x^2-12x-27=0 | | 5=5-4s-7s | | .4x-.03= | | 3x+x+40=180 | | x-20+2-(-7)=9 | | 3b-5+6b=-5 | | 1/6X-5=-11 | | 11-(8-8n)=8 | | (-16)-(-t)=(-45) | | 4(7y-3)= | | 3(2x+1)-5=10 | | 100n+10n=0n+15n | | -1(-m+n+1)= | | 1/5+1/4x=1/3x+5/6 | | -5=6x+4+3x | | 4/7=11/14x-4/7x | | 3(x+5)=3x+5+15 | | 3-10k=5b | | 1608-v=6v |

Equations solver categories